2015
DOI: 10.1097/aln.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Hyperthermia Testing in Probands without Adverse Anesthetic Reaction

Abstract: A positive CHCT may represent more than simply an anesthetic-related disorder. Individuals with positive CHCTs may exhibit muscle symptoms without exposure to MH-triggering anesthetics. Oral dantrolene may be useful in alleviating these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…A recent Canadian study of IVCT testing in probands without adverse reaction to anesthetics found MH susceptibility in 66% of 71 patients with hyperCKemia. 19 The higher frequency of MH susceptibility in our study, namely two-thirds, may be related to different ethnic characteristics (i.e., predominance of African descendants-which may also occur in the USA) and the fact that almost half of the patients in our sample exhibited muscular hypertrophy. This condition in families suspected of having malignant hyperthermia might be an indicator of both MH susceptibility and more severe MH crises.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A recent Canadian study of IVCT testing in probands without adverse reaction to anesthetics found MH susceptibility in 66% of 71 patients with hyperCKemia. 19 The higher frequency of MH susceptibility in our study, namely two-thirds, may be related to different ethnic characteristics (i.e., predominance of African descendants-which may also occur in the USA) and the fact that almost half of the patients in our sample exhibited muscular hypertrophy. This condition in families suspected of having malignant hyperthermia might be an indicator of both MH susceptibility and more severe MH crises.…”
Section: Discussionmentioning
confidence: 60%
“…There is increasing awareness of the relationship of RYR1 mutations with rhabdomyolysis and/or effort myalgia. 14,19,30 In our study, the death of relatives during surgery or physical activity was an indicator of subsequent MH susceptibility, and it is clinical information that could guide research early on towards MH. In this regard, Sunohara et al 31 reported a patient with idiopathic hyperCKemia whose sister presented with MH, and Kasi 32 emphasizes that families with idiopathic hyperCKemia should receive guidance and be investigated for MH, even if family members were asymptomatic.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to its well-established role in MH management, dantrolene has also been used in the treatment of patients with RYR1-related (exertional) rhabdomyolysis [25], and anecdotal reports suggest that some patients with RYR1-related CCD may also benefit from dantrolene use [26,27]. However, explorative use of dantrolene in RYR1-related myopathies ought probably to be limited to those carrying "leaky channel" mutations compared to those where calcium conductance is already reduced, considering that a RyR1 antagonist such as dantrolene may potentially worsen the consequences of the molecular defect in the latter group.…”
Section: Core Myopathiesmentioning
confidence: 99%
“…Chronic oral dantrolene use has been effective in decreasing the number of MH reactions in adults with this rare condition . A case of a 5‐year‐old child with congenital myopathy who was given oral dantrolene with any febrile illness has reported encouraging results .…”
Section: Discussionmentioning
confidence: 99%
“…Given the life‐threatening nature of these nonanesthesia‐related MH crises, oral dantrolene 0.5 mg·kg −1 po BID was prescribed in an attempt to prevent further nonanesthetic MH crises . After consultation with pediatric metabolics, genetics, and the regional director of the MH investigation unit, the decision was made to insert a Port‐a‐Cath ® in order to allow for early intravenous dantrolene administration.…”
Section: Case Reportmentioning
confidence: 99%